Equilibrium helium film in the thick film limit: Physics in Quantum Crystals - Klier, J.; Schletterer, F.; Leiderer, P.; Shikin, V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
For the thickness of a liquid or solid quantum film, like liquid helium or solid hydrogen, there exist still open questions about how the film thickness develops in certain limits. One of these is the thick film limit, i.e., the crossover from the thick film to bulk. We have performed measurements in this range using the surface plasmon resonance technique and an evaporated Ag film depositedon glass as substrate. The thickness of the adsorbed helium film is varied by changing the distance h of the bulk reservoir to the surface of the substrate. In the limiting case, when h → 0, the film thickness approaches about 100 nm following the van der Waals law in the retarded regime. The film thickness and its dependence on h is precisely determined and theoretically modeled.The equilibrium film thickness behaviour is discussed in detail. The agreement between theory and experiment is very good.